MicroRNA 27b-3p Modulates SYK in Pediatric Asthma Induced by Dust Mites - Dong, Xiaoyan; Zhong, Nanbert; Fang, Yudan; Cai, Qin; Lu, Min; Lu, Quan (Frontiers in Pediatrics, 2018)
The PI3K-AKT pathway is known to regulate cytokines in dust mite-induced pediatric asthma. However, the underlying molecular steps involved are not clear. In order to clarify further the molecular steps, this study investigated the expression of certain genes and the involvement of miRNAs in the PI3K-AKT pathway, which might affect the resultant cytokine-secretion. In-vivo and in-vitro ELISA, qRT-PCR and microarrays analyses were used in this study. A down-expression of miRNA-27b-3p in dust mite induced asthma group (group D) was found by microarray analysis. This was confirmed by qRT-PCR that found the miRNA-27b-3p transcripts that regulated the expression of SYK and EGFR were also significantly decreased (p < 0.01) in group D. The transcript levels of the SYK and PI3K genes were higher, while those of EGFR were lower in the former group. Meanwhile, we found significant differences in plasma concentrations of some cytokines between the dust mite-induced asthma subjects and the healthy controls. On the other hand, this correlated with the finding that the transcripts of SYK and its downstream PI3K were decreased in HBE transfected with miRNA-27b-3p, but were increased in HBE transfected with the inhibitor in vitro. Our results indicate that the differential expression of the miRNAs in dust mite-induced pediatric asthma may regulate their target gene SYK and may have an impact on the PI3K-AKT pathway associated with the production of cytokines. These findings should add new insight into the pathogenesis of pediatric asthma.